**1 a)**

We have three points.

a = (-1,2)

b = (2,3)

c = (0,0)

These form a triangle were we want to find the angles. One way to solve the problem could be to use the law of cosines, but since you're talking about vector I assume you're supposed to use the following relationship (which is derived using the law of cosines)

**u*v** = |**u**||**v**|cos(θ) (were ***** denotes the dot product)

Now we could treat a and b as vectors from the origin to the point a, respectively. Therefore we have

**a*b** = |**a**||**b**|cos(θ) => -1*2+2*3 = sqrt((-1)^2+2^2)*sqrt(2^2+3^2)*cos(θ)

Try now and come back if you still don't get the idea.